Silvopastoral systems: Mitigation of greenhouse gases in the Tropical Dry Forest - Colombia - Contreras-Santos, José Luis (2021)
Introduction. Silvopastoral systems (SSP) play a leading role in soil carbon sequestration and greenhouse gas mitigation. Objective. To quantify the ecosystem services provided by four SSPs in comparison with a grass pasture in the middle valley of the Sinú river in Colombia. Materials and methods. Methane and nitrous oxide fluxes were measured using closed chambers, during a period of eight consecutive weeks (September to November, 2013). Soil organic carbon was also measured at two depths (0-5 and 5–15 cm), by the combustion method, and soil physicochemical variables were determined. The design corresponded to randomized complete blocks with five treatments and three replications. The treatments corresponded to four silvopastoral systems made up of different tree components: Tectona grandis (SSP1), Tabebuia rosea (SSP2), Pachira quinata (SSP3) and Acacia mangium (SSP4), compared to a grass-only meadow (Megathyrsus maximus cv Mombasa). Results. The highest contents of organic matter, phosphorus, and calcium were registered within the SSP. Soil organic carbon (COS) was higher within the SSPs (39.43±15.34 t C ha-1), compared to the grassland (33.43±17.63 t C ha-1). The SSPs behaved most of the time as methane sinks, immobilizing on average -460±0.42 µg CH4 m-2 h-1. The lowest nitrous oxide emission rates were evident within SSP1 and SSP2 systems (460±0.60; 620±1.19 µg N2O m-2 h-1, respectively). Conclusion. The implementation of SSP contributes to the decrease of soil degradative processes (physical and chemical), to the increase of soil carbon stocks and, consequently, they are a greenhouse gas mitigation strategy in livestock systems.